2005
DOI: 10.1007/s11244-005-7859-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly Resolved Studies of the Reaction of Pyridine and Dimethylamine with Oxygen at a Cu(110) Surface

Abstract: Pyridine and dimethylamine have been studied at clean and oxidised Cu(110) surfaces as model systems for the interaction of amines with heterogeneous catalysts using scanning tunnelling microscopy and X-ray photoelectron spectroscopy. Both molecules interact strongly with sub monolayer concentrations of chemisorbed oxygen causing a change from the well known p(2 · 1)O(a) islands to a (3 · 1) structure. XPS shows a 1:1 correspondence between the concentration of surface oxygen and that of chemisorbed pyridine b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 53 publications
2
15
0
Order By: Relevance
“…They showed that ammonia oxida-48 tion at the b100N ends of oxygen islands was at least 100 times faster 49 than oxidation at the b110 N sides, confirming earlier predictions 50 based on Monte Carlo modeling of XPS data [13]. Extending this work, 51 we have since demonstrated the influence of oxygen islands at surfaces 52 on the pathways, kinetics, and products of a number of different reac-53 tions [16,17] but also the way in which reactants such as the amines 54 can change the local structure of the oxygen islands and thus influence 55 the reaction rate [18][19][20]. A particular interest has been to explore the 56 effect of intercepting oxygen in a transient state, i.e.…”
supporting
confidence: 74%
“…They showed that ammonia oxida-48 tion at the b100N ends of oxygen islands was at least 100 times faster 49 than oxidation at the b110 N sides, confirming earlier predictions 50 based on Monte Carlo modeling of XPS data [13]. Extending this work, 51 we have since demonstrated the influence of oxygen islands at surfaces 52 on the pathways, kinetics, and products of a number of different reac-53 tions [16,17] but also the way in which reactants such as the amines 54 can change the local structure of the oxygen islands and thus influence 55 the reaction rate [18][19][20]. A particular interest has been to explore the 56 effect of intercepting oxygen in a transient state, i.e.…”
supporting
confidence: 74%
“…These structures are not observed in the case of ammonia or aniline. The (3 · 1) oxygen/dimethylamine structure closely resembles that observed between pyridine and surface oxygen at Cu(1 1 0) surfaces [29], with evidence for a 1:1 oxygen:nitrogen ratio in both cases [32]. A similar pyridine/ oxygen complex at a Cu(1 1 1) surface was attributed [33], on the basis of HREELS data, to a pyridine oxide, but in the case of Cu(1 1 0) a direct interaction between the nitrogen and the added copper atoms of the oxygen-copper chains seems more plausible.…”
Section: Introductionsupporting
confidence: 62%
“…The formation of an intermediate complex between the amines and the surface oxygen is supported by evidence that the (3 · 1) restructured surfaces involve a 1:1 ratio of amine to surface oxygen in the cases of both dimethylamine and pyridine [32]. Vibrational data [33] from pyridine adsorption at a Cu(1 1 1) surface suggested the formation of a pyridine-oxide type compound, but on Cu(1 1 0) the added row structure results in positively charged copper adatoms closely associated with the oxygen and a more likely scenario is for an intermediate complex between Unwrapping via unstable (3 · 1) complex product À864.5 Aniline [41] No intermediates observed À850.6 Ammonia [28,51] Chain unzipping À819.0 2,2,2-Trifluoro-ethylamine Chain unzipping À813.0 a The gas phase basicity is the Gibbs free energy associated with the protonation of the neutral molecule.…”
Section: The Surface Chemistry Of Methylamine and Ethylaminementioning
confidence: 88%
See 2 more Smart Citations